Investigating AbdulHamid AbuSulayman's view on the concept of freedom based on his "Crisis in the Muslim mind" - Shehu, Fatmir Mehdi (2023)
The concept of Freedom is very diverse in nature. People of different religions, cultures, and ideologies, comprehend it in the light of their own worldview. The plurality of interpretations of this concept has created conflicts among people time and again. Scholars from different groups of people have engaged themselves in the study of this term by producing works on its understanding and practice within the framework of their own worldview or other worldviews in a descriptive or comparative approach. AbdulHamid AbuSulayman is among the contemporary Muslim thinkers, who discusses the concept of Freedom from the perspective of Islam based on the contemporary context. Therefore, this research attempts to investigate the view of AbdulHamid AbuSulayman on the concept of “Freedom” based on his masterpiece “Crisis in the Muslim Mind”. Selected text(s) related to AbuSulayman’s main views on “Freedom” and its dimensions of belief, Islamic thought, and social behavior, are identified and then analyzed. The descriptive, analytical, and critical methods are used in the entire work. A brief description of AbdulHamid AbuSulayman’s life, his intellectual development, and his work “Crisis in the Muslim Mind,” are discussed. The concept of “freedom” with emphasis on his views about the definition, characteristics, and its relationship with belief, Islamic Thought, and social behavior, is analyzed.